Strategic Optimization of Fractionation and Dialysis Buffer pH to Enhance Goat Liver-Uricase Activity - Zain, Romzi Al Amiri; Handayani, Wuryanti; Sjaifullah, Achmad; Pertiwi, Andriana Kusuma; Ratnadewi, Anak Agung Istri; Sudarko, Sudarko (Indonesian Chimica Letters, 2026)
Uricase is an important enzyme that catalyzes the oxidation of uric acid to allantoin and has potential applications in clinical diagnostics and biotechnology. However, its activity and stability are greatly influenced by purification conditions. This study aimed to optimize ammonium sulfate fractionation and the pH of the dialysis solution to enhance the activity of uricase isolated from goat liver. The enzyme was extracted and subjected to stepwise ammonium sulfate precipitation at different saturation levels, followed by dialysis using buffers with varying pH values. Enzyme activity and protein concentration were determined to calculate specific activity, and SDS–PAGE analysis was performed to evaluate the purification profile. The results showed that the optimal ammonium sulfate fraction for uricase precipitation was 0–20% saturation, yielding the highest specific activity of 0.0034 ± 0.001 U/mg. Further dialysis optimization indicated that a pH of 8.5 was the most favorable condition, yielding the highest enzyme activity of 0.0038 ± 0.001 U/mg. SDS–PAGE analysis showed reduced contaminant protein bands after purification, indicating improved enzyme purity. These findings suggest that precise control of salt concentration and buffer pH is crucial for maintaining uricase stability and enhancing its catalytic performance. Overall, the combination of optimized ammonium sulfate fractionation and dialysis conditions effectively improved the purity and activity of uricase, providing a useful basis for further development and application of this enzyme in biochemical and industrial processes.